Prenatal and Postnatal Management of Hydronephrosis - Pravin K. Rao; Jeffrey S. Palmer (The Scientific World Journal)
The majority of pregnant women in the U.S. undergo prenatal ultrasonography and approximately 0.5% of these examinations will detect fetal malformations. Up to one-half of these abnormalities include the genitourinary system and the most common urological finding is hydronephrosis. Some conditions associated with prenatal hydronephrosis portend a poor prognosis, while others can follow a fairly benign course. This review focuses on the definition and prenatal assessment of hydronephrosis, fetal intervention, and postnatal management.